2013
DOI: 10.1017/s0950268813000903
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiology ofToxoplasma gondiiinfection in the Israeli population

Abstract: Toxoplasmosis seroprevalence varies considerably between countries. We studied the seroprevalence of Toxoplasma gondii IgG antibodies in a national sample of the Israeli population; 2794 sera were tested. The highest age-adjusted seroprevalence rate was in Arabs (non-Bedouins) (60.4%), significantly higher compared to the rate in Jews (19.9%) and Bedouins (27.5%) (P < 0.01). There were no significant gender differences. Seropositivity increased with age in all population groups. For Jews, seropositivity was as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 19 publications
4
20
1
Order By: Relevance
“…Surprisingly, in the present study, there was a non-statistically significant increase in seropositivity of anti-T. gondii antibody with age of study participants. However, the observation is in agreement with other similar studies in which increasing age was more associated with chronic infection (Rosso et al, 2008, Al-Mohammad et al, 2010Markovich et al, 2014). This could be explained by the fact that older women are more likely to have been exposed much longer to any one of the risk factors than younger women.…”
Section: Discussionsupporting
confidence: 92%
“…Surprisingly, in the present study, there was a non-statistically significant increase in seropositivity of anti-T. gondii antibody with age of study participants. However, the observation is in agreement with other similar studies in which increasing age was more associated with chronic infection (Rosso et al, 2008, Al-Mohammad et al, 2010Markovich et al, 2014). This could be explained by the fact that older women are more likely to have been exposed much longer to any one of the risk factors than younger women.…”
Section: Discussionsupporting
confidence: 92%
“…Some previous reports indicated that the seropositivity of T. gondii was related to age [9,10]. Consistent with these studies, the present study showed highly significant differences in T. gondii seropositivity in the different age groups (18-45, 45-65, >65 years) in the two ethnic populations.…”
Section: Discussionsupporting
confidence: 91%
“…Regarding demographic characteristics, the T. gondii seroprevalence found in the present study was not significantly associated with any of the sociodemographic characteristics of the psychiatric patients. It has been reported that seropositivity to T. gondii is related to age [11][12][13]; however, in the present investigation, T. gondii infection in psychiatric patients was not significantly influenced by age. Although high seropositivity to T. gondii was found in the 70-79 and 580 years age groups of psychiatric patients, the number of subjects in age groups 60-69, 70-79 and 580 years was limited in this study.…”
Section: Discussioncontrasting
confidence: 89%